PLASMA RESUSCITATION PROMOTES COAGULATION HOMEOSTASIS FOLLOWING SHOCK-INDUCED HYPERCOAGULABILITY. Issue 2 (February 2016) - Cardenas, Jessica C.; Cap, Andrew P.; Swartz, Michael D.; Huby, Maria del Pilar; Baer, Lisa A.; Matijevic, Nena; Cotton, Bryan A.; Holcomb, John B.; Wade, Charles E.
ABSTRACT: Background: Increased thrombin generation in injured patients possibly contributes to early consumption of coagulation factors, exacerbating hemorrhage. Identifying optimal resuscitation products for restoring plasma homeostasis following injury is important for improving management of these patients. Objectives: To determine the effects of crystalloid versus plasma resuscitation on thrombin generation in a rat model of trauma and hemorrhagic shock (HS). Patients/Methods: Rats were subjected to trauma and HS followed by resuscitation with Lactated Ringer's solution (LR) or fresh frozen plasma (FFP). Blood was collected at baseline, decompensation, and 3-h post-resuscitation. Thrombin generation was measured by calibrated automated thrombogram and antithrombin III (AT) by ELISA. In a prospective observational study, admission blood samples were collected on highest-level activation trauma patients and diluted with LR or FFP for thrombin generation analysis. Results: Resuscitation with LR resulted in persistent hypercoagulability; however, FFP resuscitation reversed this hypercoagulability to baseline thrombin generation or below. Plasma AT levels decreased following HS and remained low in rats receiving LR, but were corrected in rats receiving FFP. Similarly, in trauma patient plasma LR increased thrombin generation while FFP reduced it. However, results with AT-deficient plasma dilution were similar to LR. In patients with admission hypocoagulability, FFP slightly increased thrombin generation. Conclusions: HS in rats is associated with increased thrombin generation and resuscitation with FFP, not LR, reverses hypercoagulability. Dilution of trauma patient plasma with LR or FFP yielded similar results; however, the modulatory effects of FFP were attenuated when AT was absent. Importantly, FFP reduced thrombin generation in hypercoagulable patient plasma, but slightly increased thrombin generation in hypocoagulable patient plasma. Thus, FFP restores hemostatic balance following trauma and HS which is, in part, by delivering AT.